Influence of winter nutrition on production and reproduction in spring-calving cows - Davis, Duane L.; Schalles, R.R.; Kiracofe, G.; Good, D.L. (Kansas State University. Agricultural Experiment Station, 2011)
Winter nutrition requirements for beef cows grazing native tallgrass range in the Flint Hills were studied from 1968 through 1973. Three lb. milo was a better supplement to the basic ration of 3 lb. alfalfa hay than 1 1/2 lb. of soybean meal was. Younger cows performed better when 6 lb. milo was fed with the 3 lb. alfalfa hay. Feeding 3 lb. alfalfa hay or the equivalent until approximately 100 days before the breeding season and 3 lb. alfalfa hay, 6 lb. milo the remainder of the winter did not reduce performance of cows 3 years old or older. Cows that rebred lost less weight over winter and were heavier the next summer when they were bred than cows that did not rebreed.
Keywords: Beef; Nutrition; Production; Reproduction